Coupling noble gas and alkane gas isotopes to constrain normally pressured shale gas expulsion in SE Sichuan Basin, China - Li, Jiaxin; Wang, Yunhai; Fang, Dazhi; Wen, Zhigang; Wu, Chenjun (Frontiers in Earth Science, 2024)
Noble gas and stable isotopes are often applied when evaluating gas accumulation and expulsion in petroleum system. In this study, stable isotopes (C, H) of alkane gases (CH4, C2H6, and C3H8) and noble gas compositions and isotopes of normally-pressured Wufeng-Longmaxi marine shale gas samples with continuous pressure coefficient series from the southeastern complex structural areas of the Sichuan Basin were systematically analyzed. The relationships between noble gas and stable isotopes with shale gas yields were evaluated and normally-pressured shale gas accumulation and expulsion mechanism was presented. For the normally-pressured shale gas, the carbon (C) and hydrogen (H) isotopes suggest the shale gas was originated from late mature thermogenic generation, same as shale gas from other shale gas production areas from the inner baisn.Gas dryness C1/(C2+C3) ratios show negative relationship with δ 13 C1 and δ 13 C2. Normally-pressured shale gas yields show negative correlation with carbon isotopes and positive correlation with dryness ratios suggesting shale gas accumulation and expulsion differential across the studied areas with various pressure coefficients. Nobel gas isotopes suggest the studied normally-pressured Longmaxi shale gas receives a significant contribution of crust-derived helium. Coupling noble gas and stable (C/H) isotopes studies revealed that the abundance of noble gases (He, Ar) and carbon isotopes of alkane gases are affected by the abundance of shale gas during accumulation and expulsion processes. Shale gas preservation conditions become better with increasing pressure coefficients and show characteristic of high shale gas yields which will dilute the concentration of noble gases. The noble gas and stable isotopes distribution trend presented in this study can be used for evaluation of Wufeng-Longmaxi normally-pressured shale gas accumulation and expulsion the southeastern complex structural areas of the Sichuan Basin.